Effects of a virtual reality-based motivational reinforcement + desensitization intervention program on psychological craving and addiction memory in female MA-dependent young adults - Ji, Xihui; Tang, Yuyao; Jing, Lushi; Zhou, Li; Wu, Binbin; Deng, Yong; Zhou, Sijin; Yang, Yangyan (Frontiers in Psychiatry, 2023)
Objectives: The aim of this study was to explore the effects of a virtual reality (VR)-based motivational reinforcement + desensitization intervention program on psychological craving and addiction memory in female methamphetamine (MA)-dependent young adults. Methods: We recruited 60 female MA-dependent young adults in a compulsory isolation drug rehabilitation facility in Sichuan Province, and randomly assigned them to intervention(mean age = 23.24±2.06) and control groups(mean age = 23.33±2.09). The intervention group received a VR-based motivational enhancement + desensitization intervention (total of eight sessions over a 4-week period), while the control group received regular detoxification management during the same period. Assessments were conducted before, immediately after, and 1 month after the intervention, with a visual analogue scale (VAS) being used to assess subjective craving, electronic sphygmomanometer employed to measure physiological parameters, and the Addiction Memory Intensity Scale (AMIS) applied to assess addiction memory intensity. Results: After the intervention, the differences in three physiological parameters, and the VAS and AMIS scores, were significantly lower in the intervention than in the control group (all p <0.05), and the difference between the two groups remained significant 1 month after the end of the intervention (both p <0.01). VAS scores, heart rate difference, and diastolic blood pressure difference in the intervention group were significantly lower than baseline scores, both at the end of the intervention and 1 month thereafter (all p <0.01); the systolic blood pressure difference in the intervention group was significantly lower at the end of the intervention than at baseline (p <0.05); AMIS scores in the intervention group were significantly lower than the baseline scores 1 month after the end of the intervention (p <0.01). Conclusion: Our VR-based motivational reinforcement + desensitization intervention program can effectively reduce psychological craving and physiological reactivity for drugs, and the intensity of addictive memories in female MA-dependent young adults, even after 1 month.